Carbamazepine - hematologic effects of the use - Kamil Leis; Ewelina Mazur; Paweł Szyperski; Tomasz Aleksiewicz; Tomasz Jamrożek; Katarzyna Lipa; Przemysław Gałązka (Kazimierz Wielki University, 2018)
Carbamazepine is an antiepileptic drug which exhibits a number of side effects, namely including a headache, abdominal pain, increased blood pressure, but also hematologic disorders. Thrombocytopenia, hypogammaglobulinemia, leukopenia, neutropenia, agranulocytosis, aplastic anemia, pure red cell aplasia, leukemia or eosinophilia with DRESS syndrome belong to the latter. There is a low incidence of carbamazepine pharmacotherapy related symptoms and their exact mechanisms of action are still unknown.